Wheat Cost-Return Budget in Western Kansas - Dumler, Troy J.; O'Brien, Daniel M.; Olson, Brian L.S. (My University, 2008)
This publication projects a budget that reflects expected income and costs based on typical production of wheat in western Kansas.
MF903_2008_10
Keywords: MF916; Economics; Crops; MF